THE INFLUENCE OF CONSUMER REVIEWS PRICES AND ONLINE ON PRODUCT PURCHASE DECISIONS IN FASHION CATEGORY IN SHOPEE "(CASE STUDY OF FACULTY OF ECONOMICS AND BUSINESS, UNIVERSITY OF MUHAMMADIYAH SUMATERA UTARA) - Rini Astuti; Anisa Permata Dewi (Journal of International Conference Proceedings (JICP), 2019)
Purchasing decisions are actions taken by consumers to make a product purchase. Many factors influence consumer purchasing decisions, including prices and online consumer reviews. This study aims to determine the effect of price and online consumer reviews on product purchase decisions in the fashion category in Shopee (Case Study of the Faculty of Economics and Business, University of Muhammadiyah North Sumatra). The population in this study were students of the Faculty of Economics and Business, Muhammadiyah University of North Sumatra (UMSU) with 100 samples of Students of the Faculty of Economics and Business, Muhammadiyah University of North Sumatra (UMSU) who had shop for fashion products at Shopee in the past 1 year. Data collection techniques use questionnaires or questionnaires that are tested for validity and reliability. The data analysis technique uses multiple regression, classic assumption test, t test, F test and coefficient of determination. Based on the data analysis and discussion in the study, the conclusions are that there is no partial price effect on purchasing decisions with tcount = 1.193 ttable = 1,984. In addition, simultaneously and significantly there is the influence of price and online consumer reviews on product purchasing decisions in the fashion category in Shopee with the value of Fcount = 47.039> Ftable = 3.09. Determination coefficient value of 0.492 or 49.2% contribution of price and online consumer reviews on product purchase decisions in the fashion category in Shopee (Case Study of the Faculty of Economics and Business, University of Muhammadiyah North Sumatra) while the remainder is 0.508 or 50.8% influenced by other variables not examined in this study.